Single-cell RNA sequencing reveals the intra-tumoral heterogeneity and immune microenvironment of small cell carcinoma of the ovary, hypercalcemic type - Yi Gao; Kewei Zheng; Haowen Tan; Mingyi Kang; Bingjian Lu; Ling Chen; Jing Xu; Chong Lu; Ranran Chai; Congjian Xu; Yu Kang (Journal of Ovarian Research)
Abstract Purpose Small cell carcinoma of the ovary, hypercalcemic type (SCCOHT) is a rare and lethal cancer lacking effective treatment. Its genomic mutations and tumor microenvironment need further exploration. Methods We performed whole-exome sequencing or gene panel test to explore the SMARCA4 mutation spectrum in SCCOHT (15 samples). Single-cell RNA sequencing was conducted on one primary lesion with matched normal ovarian tissue and one recurrent lesion to investigate the intra-tumoral heterogeneity and immune microenvironment. Multiplex immunofluorescence staining validated T cell infiltration and PD-1 expression. Results 13/15 (86.7%) patients harbored SMARCA4 mutations. The loss of heterozygosity (LOH) occurred in 10/15 (66.7%) patients. Cancer cells and immune cells were observed in SCCOHT tumors. Cancer cells were further divided into seven subtypes and one from recurrent lesion exhibited the highest stemness accompanied by high expression of genes related to cell mitosis (AURKB, CHEK2, CCNB1, WEE1), DNA repair (BRCA1, RAD51) and epigenetic (EZH2, DNMT1). Immune cells mainly included macrophages and T cells. Lipid-associated tumor-associated macrophages (TAMs) was mainly in primary lesion while inflammatory cytokine-enriched TAMs in recurrent lesion. CD4 +/ CD8 + T cell infiltration was observed in SCCOHT tumor and a certain proportion of T cells expressed PD-1. Conclusions SCCOHT exhibits universal SMARCA4 LOH and significant intra-tumoral heterogeneity, suggesting potential therapeutic targets, including CHEK2, CCNB1, and WEE1. Exhausted T cells and distinct TAM subsets infiltrate tumors. Targeting macrophage polarization or cytokine signaling may also be promising. These findings provide insights for developing novel therapies to improve outcomes in SCCOHT. Clinical trial number Not applicable.